Morphology, phenotypic profile, cytotoxicity and uptake flux of the marine microalga tetraselmis gracilis during cr (vi) exposure in controlled laboratory condition - SUCHETA SADHU; R. KIRUBAGARAN (International Journal of Pharma and Bio Sciences, 2017)
The wide range of industrial usage of chromium is a potential threat to the environment in specific to aquatic organisms. In the present study, we report the toxicity of Cr (VI) upon marine microalga Tetraselmis gracilis. Effluents from the industries, for instance leather, textile, steel, etc. release Cr (VI) which ultimately reaches to seawater, is potential route for Cr (VI) assimilation and toxicity. To comprehend the mechanism of toxicity, cells of T. gracilis was exposed in various concentrations of Cr (VI) upto 96 h. The detailed cytotoxicity assay revealed a substantial reduction of growth rate in a dose dependant manner. Significant decline in chlorophyll-a pigment and biomass was noted with increasing concentration of Cr (VI). The FTIR study suggested the surface chemical interaction of Cr (VI) with cells of T. gracilis. Further, micrometric study, photo micrographic (SEM and LM) study revealed the substantial changes in cellular morphology and cell wall damage.